2015
DOI: 10.1161/circulationaha.115.016424
|View full text |Cite|
|
Sign up to set email alerts
|

Population-Based Study of Incidence, Risk Factors, Outcome, and Prognosis of Ischemic Peripheral Arterial Events

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
126
2
11

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(143 citation statements)
references
References 43 publications
4
126
2
11
Order By: Relevance
“…Approximately 1 in 4 patients with IC will experience worsening of symptoms or the development of CLI or acute limb ischemia (ALI). These conditions are characterized by progressive (CLI) or sudden onset (ALI) of pain at rest or nonhealing ischemic wounds or gangrene [27,44,45] and can ultimately lead to a loss of limbs [46]. In the UK-based OXVASC study involving more than 90,000 general medical patients from primary care, CLI occurred at a rate of 22 events per 100,000 patients per year (mean age: 75.2 years) and ALI at a rate of 10 events per 100,000 patients per year (mean age: 76.3 years) [46].…”
Section: Peripheral Artery Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 1 in 4 patients with IC will experience worsening of symptoms or the development of CLI or acute limb ischemia (ALI). These conditions are characterized by progressive (CLI) or sudden onset (ALI) of pain at rest or nonhealing ischemic wounds or gangrene [27,44,45] and can ultimately lead to a loss of limbs [46]. In the UK-based OXVASC study involving more than 90,000 general medical patients from primary care, CLI occurred at a rate of 22 events per 100,000 patients per year (mean age: 75.2 years) and ALI at a rate of 10 events per 100,000 patients per year (mean age: 76.3 years) [46].…”
Section: Peripheral Artery Diseasementioning
confidence: 99%
“…These conditions are characterized by progressive (CLI) or sudden onset (ALI) of pain at rest or nonhealing ischemic wounds or gangrene [27,44,45] and can ultimately lead to a loss of limbs [46]. In the UK-based OXVASC study involving more than 90,000 general medical patients from primary care, CLI occurred at a rate of 22 events per 100,000 patients per year (mean age: 75.2 years) and ALI at a rate of 10 events per 100,000 patients per year (mean age: 76.3 years) [46]. In a retrospective analysis of US healthcare insurer databases, the mean incidence of CLI was 0.35% per year (in a population with a mean age of ∼69 years), representing 11.08% of patients with PAD [18].…”
Section: Peripheral Artery Diseasementioning
confidence: 99%
“…10 However, more recent work contradicts this, with a more favourable outcome in women than in men. 11,12 It is well established that smoking and comorbidities such as hypertension and diabetes increase the risk of CLTI, 13 whereas the relative impact of concurrent diseases on limb prognosis following revascularisation is less well known. A better understanding of this may improve patient selection and guide clinicians when evaluating patients with CLTI for invasive procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In a 2014 retrospective cohort study of insured adults who were at least 40 years of age, the mean annualized prevalence of PAD was 10.69%, and for CLI it was 1.33% 5 . Patients with CLI are at high risk for either minor or major amputation: a recent population-based study in the UK found that major amputation-free survival rates at 5 years after a diagnosis of CLI were only 27% 6 . Among people who undergo a major amputation, 5.7% undergo a major amputation in the contralateral limb within 1 year, with the percentage increasing to 11.5% at 5 years 7 .…”
Section: Introductionmentioning
confidence: 99%